AUTOMATIC AIR PURIFIER - SATHISH, K.; ARCHANA, B.; RAM, B.SURESH; VARSHINI, P.; CHANDRA, S.BHARATH (The journal of contemporary issues in business and government, 2022)
Air pollution is a mixture of solid particles and gases in the air. Car emissions, chemicals from factories, dust, pollen and mold spores may be suspended as particles. OZONE, a gas, is a major part of air pollution in cities. When ozone forms air pollution, it’s also called smog. If the air quality index (AQI) reports are anything to go by, then the quality of air in most cities of India is deteriorating day by day. As the winter months of October and November approach, the air quality outdoors becomes worse since the pollution that is generated from various sources gets trapped because of differences in air pressure, moisture and wind speeds. This also tends to have a direct influence on the indoor air quality in home or office spaces here most individuals tend to spend approximately 90% of their time. In the past decade or so, the home air purifier market has shifted multiple gears as an affordable solution for indoor air quality. Besides this, there have been seemingly ground breaking advancements in filtration technologies ensuring the development of the next level in air purifier.